PenÄ±ngkatan MotÄ±vasÄ± Kerja Guru MelaluÄ± Metode SupervÄ±sÄ± AkademÄ±k - Sri Kis Untari (Universitas PGRI Adi Buana Surabaya, 2021)
This study is to determine the effectiveness of the use of supervision methods in increasing the motivation of teachers at SD Negeri Margorejo I / 403 Surabaya. Respondents amounted to 51 teachers. This research is a school action research (PTS) which is conducted during the learning process. The research method is PTS. PTS procedure, namely Planning-Action-Observation-Reflection. Data obtained by using interviews. In addition, classroom observations were also carried out by researchers. Data were analyzed descriptively. The results show that the use of the supervision method for teachers at SD Negeri Margorejo I / 403 is effective in increasing teacher motivation. Evidenced by the results of the mean value of 89.75. It is concluded that using the supervision method brings changes in the conditions of the motivation to joke in the field practice.